The Development of Interactive Media Based Wirdah Learning Model - Yanti Nasution, Wirdah; Napitupulu, Efendi; ., Baharuddin; Simarmata, Janner (International Journal of Engineering and Technology, 2018)
This study aimed to find out the feasibility of interactive media-based learning model and the effectiveness of interactive media-based learning model in m Enhancing student learning outcomes. This learning product development model was a model structured in a programmed and systematic sequence and fulfilled the characteristics of students in learning. The results showed (1) test of Civics subject matter experts were at very good qualifications of 96.1%, (2) test of design experts with excellent qualifications of 97.27%, (3) test of software experts at very good qualifications 96 , 1%, (4) individual trials were in excellent qualifications of 92.3%, (5) small group trials were in very good qualifications of 93.9%, (6) field trials were in very good qualifications of 97, 61%. The results of testing the hypothesis proof that there were significant differences between student learning outcomes in the control class and the experimental class. This was indicated by the results of data processing tobserved = 1.97 , at the significance level Î± = 0.05 ttable = 1.69. It was concluded that interactive media-based learning models that were developed were feasible and effective to improve Civics learning outcomes.Â Â